Effect of catalase on CPC production during fermentation of Acremonium chrysogenum - Ling Liu; Zhen Chen; Xiwei Tian; Ju Chu (Bioresources and Bioprocessing)
Abstract Cephalosporin C (CPC) is a critical raw material for cephalosporin antibiotics produced by Acremonium chrysogenum. During fermentation, the oxygen supply is a crucial factor limiting the efficient biosynthesis of CPC. This study demonstrated that the addition of exogenous surfactants significantly increased the dissolved oxygen (DO) level, extracellular catalase content, and final CPC titer. Consequently, we hypothesized and examined a correlation between catalase and CPC biosynthesis in A. chrysogenum through both the exogenous addition of hydrogen peroxide (H₂O₂) and the endogenous modulation of the catA expression level. The results indicated that both the addition of H₂O₂ and the ∆catA mutation exhibited similar fermentation trends, leading to decreased extracellular catalase activity and increased intracellular reactive oxygen species (ROS) content, which resulted in reduced CPC production. Conversely, strains that overexpress varying levels of the catA accelerated hyphal differentiation under DO-limiting conditions, reducing intracellular ROS accumulation and decreasing cellular apoptosis, which stabilized CPC yield during the later stages of fermentation. This study provides a critical foundation for further investigations into the regulatory mechanisms governing CPC biosynthesis in A. chrysogenum. Graphical Abstract